Pengaruh Pemberian Kombinasi Ekstrak Kulit Pisang dan Kulit Nanas terhadap Indeks Organ Tikus Wistar - Melania Niken Safira; Pratiwi Apridamayanti; Hadi Kurniawan; Inarah Fajriaty; Fajar Nugraha; Siti Nani Nurbaeti; Liza Pratiwi (State University of Gorontalo, 2022)
Banana peel and pineapple peel contain potassium which may be developed into health supplements. The development of banana peels and pineapple peels as ingredients for potassium supplements must meet safety aspects that can be proven by subchronic toxicity tests. This subchronic toxicity test aimed to determine the effect of repeated administration of a combination of banana peel and pineapple peel extract for 28 days on the liver, kidney, kidney, lung, heart, and spleen index of Wistar rats. This research used male and female white rats which were divided into six treatment groups, namely the control group, low dose, middle dose, high dose, satellite control, and high dose satellite. The results showed that there was a significant increase in the liver and kidney organ index, and a significant decrease in the adrenal gland organ index after administration of a combination of banana peel and pineapple peel extract. This research concludes that the combination of banana peel and pineapple peel extract has an effect on the liver, kidney, and adrenal gland organ index in Wistar white rats.